Produção de saberes docentes em Ciências Naturais : abordagem de um estudo etnográfico na prática pedagógica de professores dos anos finais do ensino fundamental - Cravo, Maria José de Souza (2019)
The present research is situated in knowledge production context and teachers‟ practices of natural sciences with the purpose of highlighting the knowledge developed by them in the daily life of their work, having as a starting point the question: How the Science Teachers from the Municipal Education Network of Belém articulate their knowledge to (in) the production of their practices? Thus, the research aimed to investigate the mobilized knowledge by the Natural Sciences teachers of the final years of Elementary School from the Municipal Public Network of Belem in the production of their pedagogical practices. In the theoretical foundation, the following themes are addressed: The practice of Science Teaching in the diverse pedagogical tendencies of Brazilian education. Teachers training: a look at science teaching. Teaching practice and knowledge. The methodological course includes the context, which are the schools of the Public School of Education from Belem with offer of the 6th to 9th grade of Elementary School. The four participants of the research are the Natural Science Teachers of the final years of Elementary School, Technical of the Board of Education (DIED) from SEMEC that works with the continuing education and Pedagogical Advisors of the schools field of research. The choice was made for the qualitative approach and the Subjectivist Interactionist Approach (Gauthier, et al 2013), as well as for the study of the ethnographic type. To obtain the data, the questionnaire, the semi-structured interview, the participant observation and the documentation were used. The data were analyzed according to Bardin (2006), the categories being established from the data analysis in each context unit. The interpretation of the data occurred by the construction of the theoretical basis based on the data and the categories derived from them. The Curricular Guidelines for Elementary Education - Cycles III and IV from SEMEC are analyzed, with regard to the teaching of Natural Sciences, in order to enable the vision of what the Education System expects from science teachers in terms of performance and educational results. The spaces provided by SEMEC / the School where the teachers are part of a typical scenario of the traditional teaching pattern, designed to meet the requirements of the teaching model based on technical rationality. The Continuing education is deficient and compatible with traditional teaching, reinforcing the conception that the figure of an external teacher is always necessary. Regardless of this context, it was possible to identify all categories of Tardif's typological model in teachers' practices, with emphasis on experiential knowledge; these practices have characteristics attributed to the reflexive teacher model. A category, abstracted from the statements and actions of all the participants, demonstrates a feeling of solidarity with the students, influencing decisively the knowledge construction and practices of these teachers.